2014
DOI: 10.1158/1078-0432.ccr-13-1943
|View full text |Cite
|
Sign up to set email alerts
|

Modeling RAS Phenotype in Colorectal Cancer Uncovers Novel Molecular Traits of RAS Dependency and Improves Prediction of Response to Targeted Agents in Patients

Abstract: Purpose KRAS wild-type status is an imperfect predictor of sensitivity to anti-EGFR monoclonal antibodies in colorectal cancer (CRC), motivating efforts to identify novel molecular aberrations driving RAS. This study aimed to build a quantitative readout of RAS pathway activity to: (1) uncover molecular surrogates of RAS activity specific to CRC; (2) improve the prediction of cetuximab response in patients; (3) suggest new treatment strategies. Methods A model of RAS pathway activity was trained in a large C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…Thus, ΔPC1.EMT captures both epithelial and CSC features, which are supported by a recent report demonstrating that in breast cancer, CDH1 and CD24 were highly enriched in the epithelial CSCs ( ALDH1 -positive), while their expression was down-regulated in the mesenchymal CSCs ( CD44 + CD24 -)(33). ERBB3 , a member of the EGFR family (34), was also identified as one of the genes whose contribution was increased in ΔPC1.EMT (Figure 3C). In agreement with thi s , we observed that ΔPC1.EMT, but not EMT, was associated with activation of the RAS/MAPK pathway, evidenced by its positive correlation with various RAS signature scores (Supplementary Table S10).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, ΔPC1.EMT captures both epithelial and CSC features, which are supported by a recent report demonstrating that in breast cancer, CDH1 and CD24 were highly enriched in the epithelial CSCs ( ALDH1 -positive), while their expression was down-regulated in the mesenchymal CSCs ( CD44 + CD24 -)(33). ERBB3 , a member of the EGFR family (34), was also identified as one of the genes whose contribution was increased in ΔPC1.EMT (Figure 3C). In agreement with thi s , we observed that ΔPC1.EMT, but not EMT, was associated with activation of the RAS/MAPK pathway, evidenced by its positive correlation with various RAS signature scores (Supplementary Table S10).…”
Section: Discussionmentioning
confidence: 95%
“…In agreement with thi s , we observed that ΔPC1.EMT, but not EMT, was associated with activation of the RAS/MAPK pathway, evidenced by its positive correlation with various RAS signature scores (Supplementary Table S10). Thus, we speculated that ΔPC1.EMT-associated poor prognosis might, in part, result from RAS/MAPK activation-mediated drug resistance (34) in epithelial-like CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in PIK3CA mutation status during treatment with anti-EGFR drugs have previously been described, although a clear correlation with resistance to anti-EGFR mAbs was not identified (17). Mutations in FBXW7 have been recently reported as potential markers of resistance to anti-EGFR mAbs (18). However, the disappearance of the FBXW7 mutation from cells following response to cetuximab-based therapy argues against this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning has been applied to gene expression in a variety of studies with various goals [37][38][39][40][41]. In a similar study, Guinney et al trained a classifier to model RAS activity in colorectal cancer and demonstrated its clinical utility by predicting response to MEK inhibitors and anti-EGFR based treatments [18]. With a wealth of signal embedded in gene expression and a rapidly growing library of datasets, the performance of machine learning models is likely to rapidly improve.…”
Section: Discussionmentioning
confidence: 99%
“…We chose a penalized regression model because it is simple to train and has easily interpretable outputs including importance scores for each gene (feature weights) associated with the downstream consequences of NF1 loss of function and a probability for each sample that NF1 is lost. An elastic net logistic regression model has also been successfully implemented in similar studies [18][19][20].…”
Section: Hyperparameter Optimization Of the Logistic Regression Classmentioning
confidence: 99%